Penjadwalan Job Shop Dengan Pendekatan Algoritma Artificial Immune System - Nasution, Riven; Garside, Annisa Kesy; Utama, Dana Marsetiya (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
Production scheduling is an important activity in manufacturing. Optimal scheduling affects the time of completion of the work. PT. Interpack is a company that produces packaging machines. The job schedule of the product spare part still uses the random priority rules. Use of random rules makes a lot of time delay. Delay causes operator and machine idle. Delay also causes the total time of completion of the work (makespan) and delay the greater.Â So it needs to be rescheduled to work on the spare part of product. Job scheduling using the Artificial Immune System (AIS) algorithm. AIS was developed by Farmer et al. The AIS algorithm refers to the human immune system. The stages of the AIS algorithm begin with random initialization, antibody representation and gene classification, clone breeding, selection of donor antibodies, germ-line construction, gene fragment redesign, and ending with diversification of antibodies. AIS algorithm scheduling resulted in a more optimal new schedule. AIS algorithm scheduling generates a future of 6483.91 minutes. Company scheduling generates makespan of 7059.99 minutes. AIS Schedule finishes algorithm 4 days of the due date. AIS algorithm schedule increase machine utility by 1%.